Fruit quality and occurrence of mildew in Niagara Rosada grown under plastic cover and defoliation rates - Solivan Rosanelli; Fabíola Villa; Daniel Fernandes da Silva; Maria Cristina Copello Rotili; Tatiane Eberling (Revista Ceres)
ABSTRACT The purpose of this study was to evaluate the agronomic behavior of the Niagara Rosada variety cultivated under plastic cover, using defoliation intensities, and its influence on the Plasmopara viticola. The experiment was conducted in Francisco Beltrão, PR, Brazil, in a vineyard of Niagara Rosada variety in a trellised system during the 2016/2017 and 2017/2018 crop seasons. The experimental design consisted of randomized blocks, in a 5 x 2 factorial scheme being five percentages of defoliation (0%, 10%, 20%, 30% and 40%,) and use of coverage (with and without coverage), with three blocks of three useful plants per experimental plot. The temperature, air humidity and incidence of mildew on the bunches and leaves were recorded. At the end of each crop station, three bunches per plant of each plot were evaluated for the fresh biomass of the bunches, length and width of the bunches, soluble solids content, pH, number of bunches per plant, production, and productivity. It was concluded that the plastic cover associated with the environmental conditions, and phytosanitary management can favor the physical-chemical quality and reduce the severity of the mildew in the Niagara Rosada variety providing greater production and productivity. The use of defoliation does not favor the cultivation of this variety in southwestern Paraná.